The Secret Formula for Getting Rich with Scientific Research using Academic Marketing: Prepare to be Amazed! - Pontes, Felipe (Advances in Scientific and Applied Accounting, 2023)
Objective: How do internet searches work? Have you ever thought about how things could be different if you marketed your research better? In this editorial, I seek to challenge the more restrictive narrative of scientific production and scientific dissemination by blending theory with practical examples, inviting you, the reader, to try a more targeted digital engagement, turning your research into an open conversation with users in general, not just a monologue confined to the digital shelves of journals, merely accumulating points for CAPES. Method: Leaving the comfort zone of impersonal, third-person writing, in this editorial, we will dive into the rediscovered art of “selling” research to the public. Results: I initially unravel the mystery of the search algorithm, with a touch of academic marketing, to spice up the quest for online visibility. Contributions: Among strategies of Academic Search Engine Optimization (ASEO) and reflections on the reluctance of some academics towards marketing, I propose that we revisit our view of how research can be “sold” to the market. Additionally, I bring some implicit and explicit ideas for research that could be conducted along this line of more effective scientific dissemination.